The Management For Halal Certification Of Imported Meat In Johor: An Overview Of Standard Operating Procedures (sops) - Nur Damia Shaira Harsual Effendi; Setiyawan Gunardi (Tazkiyyah Global Enterprise., 2025)
Non-Indexed Publication